The Influence of Cinematography on the Emotional Sphere of Personality of Adolescent - Predko, Viktoria; Korduban, Kateryna; Predko, Denys (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article reveals the specifics of the influence of film genres, such as horror, comedy, drama, science fiction and detective on the personality of a teenager. It is noted that each genre of the film has a unique effect on the psyche, moreover, the preference for one or another genre is determined by the internal needs of the individual, his mental state and unconscious experiences.The positive and negative features of the influence of cinema on adolescents' behavior are considered. It has been determined that a violent, aggressive, and often even meaningless or immoral film can be used to demonstrate abnormal, destructive behavior. It is noted that the main psychological mechanism of the positive influence of cinema on the personality of an adolescent is the discussion of the film, which leads adolescents to a constructive analysis of their experiences, providing "immunity" to the possible negative consequences of destructive films. It is emphasized that feedback after watching a film can not only reduce the negative impact of on-screen images but also provoke reflection and form internal patterns of behavior.The article presents the results of a study of the influence of cinema on the emotional area of an adolescent. In particular, the results were compared before and after watching the film. It was found that after watching the film, the subjects' level of anxiety slightly increased, but their level of energy, their level of elation and confidence also increased. That is, despite a slightly increased level of anxiety, it can be argued that the film had a positive effect on the emotional state of the subjects. After watching the film, teenagers showed emotional upliftment and self-confidence.The decisive role of cinema in the purposeful development of a teenager is emphasized, namely, modeling his strengths of character, forming his own life position, as well as establishing interpersonal and intergroup relationships, the ability to change infantile views to new, mature worldview positions, to form moral and aesthetic values.
Keywords: personality; adolescent; development; cinematography; positive influence; emotional sphere